Expression of CDw12 and CD17 cell surface antigens on leukemic cells from patients with blood malignancies - Marinov, J; Koubek, K; Starý, J (Folia biologica, 1993)
In 67 cases of newly diagnosed blood malignancies, NonT-ALL, T-ALL, AMLL, AML, CML, CLL, HCL, PLL, MDS, B splenic lymphoma, AUL, as well as in 9 cell lines (U937, HEL, Jurkat, HL60, UHKT2, KG1, Raji, K562, REH), we have analysed the expression and distribution of 2 relatively incompletely studied antigenic markers from the CD nomenclature: CDw12 and CD17, individually and in combination with well characterized ones. We present our data for the usefulness of these molecules in immunodiagnosis of leukemias and lymphomas.
Keywords: antigeny povrchové; CD antigeny; lidé; Bone Marrow; lymfom; Hematologic Diseases; krevní nemoci; nádorové buňky kultivované; Immunophenotyping; Antigens, CD; imunofenotypizace; kostní dřeň; Lymphoma; Tumor Cells, Cultured; nádorové biomarkery; leukemie; Leukemia; Biomarkers, Tumor; Antigens, Surface; Humans